Technology and Price Structure in General Interdependence Systems - Zarnowitz, Victor (Review of Economic Studies, 1955)
Journal Article Technology and Price Structure in General Interdependence Systems Get access Victor Zarnowitz Victor Zarnowitz New York, N. Y. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 23, Issue 2, 1955, Pages 109–125, https://doi.org/10.2307/2296294 Published: 01 January 1955